Diplomacy by Russia, Diplomacy by Serbian. The First Soviet’s Representatives in Belgrad, and the First Yugoslav’s representatives in Moscow - A. Y. Timofeev (Vestnik MGIMO-Universiteta, 2009)
USSR and the Kingdom of Yugoslavia didn’t have any diplomatic relations till 1940 from the moment of their creation after the First World War. Belgrade has to change its anticommunist policy only after the fall of France and in 1940 the diplomatic relations were established. Comparing of Russian and Yugoslav diplomats’ biographies and diplomatic activities is an adequate way to understand a role of subjective factor and mutual stereotypes in the further contacts between Moscow and Belgrade.